Tinjauan Awal Terhadap Modul Teras Fiqh Forensik Bagi Kegunaan Pegawai-Pegawai Syariah Di Malaysia (A Preliminary Review on Fiqh Forensics Fundamental Module for the Use of Shariah Officers in Malaysia) - Baharuddin, Ahmad Syukran; Wan Ismail, Wan Abdul Fattah; Abdul Mutalib, Lukman; Ahmad, Muhammad Hazim; Mohd Nasir, Badlihisham; Wan Harun, Mohamad Amir (UMRAN - Journal of Islamic and Civilizational Studies, 2019)
The advancement in the field of forensic science highly affects the legal and enforcement field. As for the Shariah law, Syariah officers in Malaysia face challenges in controlling scientific-based exhibits and evidence. This has been seen as a result of lack of exposure, knowledge and comprehensive training in evidencing procedures using scientific-based qarinah. This preliminary study discusses the proposal to establish fiqh forensics fundamental module for the use of Syariah officers in Islamic legal institutions in Malaysia. This qualitative study applied inductive and deductive approaches in obtaining general and specific conclusion from primary and secondary sources. The findings show that there is a need to propose for the development of a specific module to empower human capital which includes enforcement, shariah prosecutors, judges and registrars within the integration framework of forensic science integration and fiqh based on the concept of 'fiqh forensics'. As such, this study addresses the proposed development of the fiqh forensics fundamental module for the use of shariah legislation.